SHIFTING MOTIVATIONS AMONG STUDENTS WHILE INDUSTRIAL TRAINING: MAINTAINING STUDENTS' LEARNING OF MANDARIN - Avenida, Quinta; Septi K., Dani Putri; Phanata, Stephanie; Rahayu, Kristina Indah Setyo (Journal of Community Service, 2023)
This study, which was covered in the paper, looked at how Diploma in Mandarin students' motivation for learning Mandarin changed before and after they were relocated to China. In the investigation, we urged the 15 participants to keep reflective journals and interviewed them twice, once before and once after their industrial training experience at PT Formosa Bag Indonesia. The research showed that the majority of participants projected to maintain their trip-induced increases in desire for learning Mandarin in the future. The results show that the participants' motivations changed during their industrial training at PT Formosa Bag Indonesia, and that this change was prompted by their new educational environment and individual learning experiences. Because the learning and sociocultural environments are always interacting with the participants' L2 self-concepts in industry, the motivational boost evolved. These results provide novel insights into the dynamic motivation for learning the Mandarin language as well as the function of formal and informal learning environments. They imply that in order to increase international students' motivation for long-term Mandarin study, educational stakeholders must offer genuine communication chances and resources.